TANGGUNG JAWAB HUKUM PENGELOLA HUNIAN TERHADAP PENGAWASAN IZIN TINGGAL WARGA NEGARA ASING DI WILAYAH HUNIAN APARTEMEN - Laela, Sofa; Rakasiwi, Galih (IBLAM LAW REVIEW, 2021)
Fulfilling the housing needs for foreign nationals in Indonesia is not only limited to houses on the ground but also regular houses such as apartments. In the context of the supervisory function of the presence of foreigners in Indonesia who live in apartments, it is necessary to have the participation of apartment dwelling managers in assisting the government by providing reports on their whereabouts. The problem in this research is how is the legal responsibility of residential managers in reporting the presence of foreigners living in apartment dwellings and what are the legal sanctions for apartment dwelling managers who do not report the presence of foreigners living in apartment dwellings. The problem approach in this study was carried out using a normative and empirical juridical approach. The results of the study stated that the mechanism for managing residence permits for foreign nationals in apartment dwellings was carried out with rules that had been made by the apartment dwelling managers themselves but still had to coordinate with relevant agencies, namely companies where foreigners work and also with the local government, especially the immigration authorities. Meanwhile, regarding the sanctions for apartment dwelling managers who do not report the presence of foreigners living in their apartment dwellings, Article 117 of Law Number 6 of 2011 concerning immigration.